Journalistic Genres across Europe and Brazil: a Vanishing Category - Gradim, Anabela (Opción, 2016)
Journalistic Genres, once a core discipline in journalism graduation courses, is being replaced in many curricula by the teaching of media-embedded reporting techniques. Instead of learning on genre and type reporting techniques, many graduation courses rely no more on the practice of traditional journalistic genres, preferring to include instead media practices in their curricula such as radio, television and web reporting. This paper maps the extension of the discipline”™s teaching in Portugal, Spain, Brazil, and Northern Europe”™s graduation courses ”“ showing Journalistic Genres are surviving at different rates, and are a vanishing category in northern countries.